1999
DOI: 10.1128/jcm.37.11.3756-3758.1999
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Revised MicroScan Dried Overnight Gram-Positive Identification Panel To Identify Enterococcus Species

Abstract: The revised MicroScan Dried Overnight Gram-Positive Identification panel was evaluated for its efficacy at identifyingEnterococcus species in comparison with conventional biochemical tests. Supplemental testing of ampicillin-susceptibleEnterococcus faecium for motility and the ability to acidify methyl-α-d-glucopyranoside helped recognizeE. gallinarum and increased the accuracy of the panel for identifying Enterococcus species to 98.5%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The identification accuracy for all other species is low and performing supplemental tests to achieve sufficient accuracy is recommended (Cartwright et al. 1995; Iwen et al. 1999; D'Azevedo et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification accuracy for all other species is low and performing supplemental tests to achieve sufficient accuracy is recommended (Cartwright et al. 1995; Iwen et al. 1999; D'Azevedo et al.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown their performance to be variable, with limited accuracy for determining Enterococci species except for Enterococci faecalis , the most commonly isolated clinical strain (Cartwright et al. 1995; Iwen et al. 1999; Garcia‐Garrote et al.…”
Section: Introductionmentioning
confidence: 99%